Factors associated with blood loss in orthognathic surgery. - Cordero Peña, Grover (2022)
Orthognathic surgery is a surgical procedure that generates intraoperative blood loss, which is why the oral and maxillofacial surgeon is constantly generating new techniques and technologies for the reduction of intraoperative blood loss. Objective: To determine the factors associated with intraoperative blood loss in orthognathic surgery. Material and Methods: It is a retrospective, descriptive, cross-sectional and analytical study. Sixty medical records of patients operated of orthognathic surgery were reviewed that met the selection criteria. The dependent variable was intraoperative blood loss and the covariates: type of orthognathic surgery, operator: Maxillofacial surgeon or resident of the program in maxillofacial surgeon, cutting instruments, operative time, prothrombin time, thromboplastin time, platelet count, age and sex. The statistical tests ANOVA, Student’s t, Spearman’s Rho and Pearson’s correlation were applied. Results: There is a significant difference in Intraoperative blood loss and operative time in relation to the operator who performed the surgery (p<0.005) and (p<0.001) there is also a direct correlation between intraoperative blood loss and operative time (p<0.05). Conclusions: The operator and the TO are variables directly associated with the PSI in the orthognathic surgery.